Association of Inflammatory and Oxidative Status Markers with Metabolic Syndrome and Its Components in 40-to-45-Year-Old Females: A Cross-Sectional Study - Katarína Šebeková; Marta Staruchová; Csilla Mišľanová; Aurélia Líšková; Mira Horváthová; Jana Tulinská; Miroslava Lehotská Mikušová; Michaela Szabová; Radana Gurecká; Ivana Koborová; Melinda Csongová; Tamás Tábi; et al. (MDPI AG, 2023)
Oxidative stress and sterile inflammation play roles in the induction and maintenance of metabolic syndrome (MetS). This study cohort included 170 females aged 40 to 45 years who were categorized according to the presentation of MetS components (e.g., central obesity, insulin resistance, atherogenic dyslipidemia, and elevated systolic blood pressure) as controls not presenting a single component (n = 43), those with pre-MetS displaying one to two components (n = 70), and females manifesting MetS, e.g., ≥3 components (n = 53). We analyzed the trends of seventeen oxidative and nine inflammatory status markers across three clinical categories. A multivariate regression of selected oxidative status and inflammatory markers on the components of MetS was performed. Markers of oxidative damage (malondialdehyde and advanced-glycation-end-products-associated fluorescence of plasma) were similar across the groups. Healthy controls displayed lower uricemia and higher bilirubinemia than females with MetS; and lower leukocyte counts, concentrations of C-reactive protein, interleukine-6, and higher levels of carotenoids/lipids and soluble receptors for advanced glycation end-products than those with pre-MetS and MetS. In multivariate regression models, levels of C-reactive protein, uric acid, and interleukine-6 were consistently associated with MetS components, although the impacts of single markers differed. Our data suggest that a proinflammatory imbalance precedes the manifestation of MetS, while an imbalance of oxidative status accompanies overt MetS. Further studies are needed to elucidate whether determining markers beyond traditional ones could help improve the prognosis of subjects at an early stage of MetS.